Literatur Review : E-Learning Dan Aplikasinya Dalam Bidang Pendidikan Keperawatan - Koko Wahyu Tarnoto (Poltekkes Kemenkes Surakarta, 2018)
Background: The development of information technology has an impact on the world of education in terms of learning systems. E-Learning (Electronic learning) is a webbased virtual education system that has the purpose of helping the process of teaching and learning activities. The method used in this literature study is the type of nonsystematic review. Method: The author searches for the electronic database PROQUEST, Science Direct, Elsevier, BMJ, Google Scholar and PubMed. The author also uses several search keywords namely